Revealing novel cytb and nad5 genes-based population diversity and benzimidazole resistance in Echinococcus granulosus of bovine origin - Alvi, Mughees Aizaz; Alshammari, Ayed; Ali, Rana Muhammad Athar; Ul Haq, Shahbaz; Bashir, Rizwan; Li, Li; Saqib, Muhammad; Sajid, Muhammad Sohail; Ghafoor, Muzafar; Imran, Muhammad; Ijaz, Muhammad Umar; Fu, Bao-Quan; et al. (Frontiers in Veterinary Science, 2023)
Cystic echinococcosis (CE) is a neglected zoonotic disease caused by Echinococcus granulosus (sensu stricto). The parasite affects a wide range of livestock and wild animals. In this study, the population diversity of the Echinococcus species was investigated based on mitochondrial cytochrome b (cytb) and NADH dehydrogenase subunit 5 (nad5) genes. In addition to this, β-tubulin gene isoforms of Echinococcus granulosus were amplified to determine the resistance against benzimidazoles. For this purpose, 40 cyst samples from cattle (n = 20) and buffaloes (n = 20) were collected from the main abattoir of Sialkot. DNA extraction was performed using Qiagen Blood and Tissue Kits. Amplification was performed through PCR. Each amplicon was confirmed by GelRed™ stained agarose gel (2%). Samples were sequenced in a DNA analyzer and viewed for any misread nucleotide by using MEGA (v.11). Corrections in nucleotide sequence and multiple sequence alignment were made through the same software. NCBI-BLAST was used for sample specific sequences to identify them as belonging to a particular species. Diversity indices were estimated using DnaSP (v.6) while phylogenetic analysis was inferred using the Bayesian method using MrBayes (v.1.1). β-tubulin gene isoforms sequence analysis was performed to find out the candidate gene causing benzimidazole resistance. All 40 isolates were found positive for E. granulosus. BLAST-based searches of sequences of each isolate for each gene (nad5 and cytb) confirmed their maximum similarity with the G1 genotype. Overall, high haplotype diversity (Hd nad5 = 1.00; Hd cytb = 0.833) and low nucleotide diversity (π nad5 = 0.00560; π = cytb = 0.00763) was identified based on diversity indices. For both the genes, non-significant values of Tajima’s D (nad5 = −0.81734; cytb = −0.80861) and Fu’s Fs (nad5 = −1.012; cytb = 0.731) indicate recent population expansion. Bayesian phylogeny-based results of nad5 and cytb sequences confirmed their genotypic status as distinct from other Echinococcus species. This study shed light on the status of benzimidazole resistance in Echinococcus granulosus for the very first time from Pakistan. The findings of this study will significantly add in the information available on genetic diversity of Echinoccous granulosus based on cytb and nad5 genes sequences.